Bifidobacterium infantis and bifidobacterium breve improve symptomatology and neuronal damage in neurodegenerative disease: A systematic review (2025)
Background/Objectives: This systematic review focused on collecting the most significant findings on the impact of the administration of Bifidobacterium infantis (or Bifidobacterium longum subps. infantis) and Bifidobacterium breve, alone, in conjunction, or in combination with other strains, in the treatment of neurodegenerative diseases including Alzheimer’s disease (AD) and Parkinson’s disease (PD). These diseases are characterized by the progressive degeneration of neurons, resulting in a broad spectrum of clinical manifestations. AD is typified by a progressive decline in cognitive abilities, while PD is marked by motor symptoms associated with the loss of dopamine (DA). Methods: Five different databases, ScienceDirect, Scopus, Wiley, PubMed, and Web of Science (WoS), were reviewed and the studies were screened for inclusion by the following criteria: (i) studies that specifically evaluated the use of Bifidobacterium infantis, Bifidobacterium longum subsp. infantis, or Bifidobacterium breve as a therapeutic intervention, either in human or animal models, in the context of neurodegenerative diseases; (ii) the studies were required to address one or more of the pathologies examined in this article, and the pathologies included, but were not limited to, neurodegeneration, Alzheimer’s disease, Parkinson’s disease, and oxidative stress; (iii) the full text was accessible online; and (iv) the article was written in English. Results: The data suggest that these probiotics have neuroprotective effects that may delay disease progression. Conclusions: This study provides updated insights into the use of these Bifidobacterium strains in neurodegenerative diseases like AD and PD, with the main limitation being the limited number of clinical trials available.